Clinical Pharmaceutical Safety and Healthcare Systems Management- An Updated Review Article For Pharmacists, Health Securities, and Medical Maintenance Specialists - Alhazmi, Salem Qyyadh; Nasser Ahmad Mobarki; Sukianh Abdultef Alalaq; Haila Mohammed Fahad Alhaerthi; Noura Obaid Khazam Al-Otaibi; Mohammed Jaber Abdullah Ali; Nouf Abdulqader Hassan; Jawaher Homoud Alanazi; Ahmed Hameed Alamri; Majed Mousa Mohammed Sulayyi; Abdulaziz Saud Alhazmi; Mohammed Radhi M; et al. (Saudi Journal of Medicine and Public Health, 2025)
<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Background:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Healthcare is a safety-critical industry where preventable harm remains a major public health concern. Learning from high-risk sectors like aviation and nuclear power, safety management systems (SMS) offer a proactive, systematic framework for managing safety through organizational structures, risk management, and continuous improvement. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Aim:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> This review was commissioned to inform the development of the NHS England's patient safety policy. It aims to synthesis evidence on SMS in healthcare to address three key questions: the attributes of a successful NHS SMS, the links between an SMS and quality management, and the next steps for safety management in the NHS. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Methods:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> The study conducted a comparative review of national patient safety approaches, analyzing systems in the Netherlands, Australia, Canada, Ireland, and New Zealand, with a focus on the integration of SMS principles. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Results:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> The Netherlands was the only country with a mandatory, certified SMS for hospitals, which was associated with a reduction in preventable adverse events. Other countries embedded core SMS components—such as leadership, risk management, and safety assurance—within national standards and accreditation frameworks but did not mandate a formal SMS. Evidence from the Dutch programme showed improvements, though outcomes were influenced by contextual factors like implementation support and concurrent initiatives. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Conclusion:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Core SMS principles are transferable to healthcare and can contribute to improved safety outcomes. However, successful implementation requires significant contextual adaptation, strong leadership, and robust supporting infrastructure, rather than simply adopting a generic model.